Determinación de la prevalencia de parásitos intestinales en caninos en Guaranda - Poma Manobanda, Evelin Lizbeth (2021)
In the present investigation, the prevalence of intestinal parasites in Guaranda canines was determined. The objectives were to verify the prevalence of intestinal parasites in canines according to their, race, sex, age and type of diet in Guaranda, Casipamba and Vinchoa, establish the infecting parasite load in the canine population using the Willis flotation method and sedimentation method, characterize the zoonotic-infecting intestinal parasites in Guaranda, Casipamba and Vinchoa. We determined the prevalence of gastrointestinal parasites in the three sectors under study, for Casipamba a prevalence of 68.3% was determined, for Guaranda 45% and for Vinchoa 76.7%, for a total parasite prevalence of 63.3 for all the experimental phase. We established that 47.4% of the total samples presented a slight parasite load (++) of 4-7 eggs / field, 39.5% corresponded to a moderate parasite load (+++) of 8-10 eggs / field, 10.5% belonging to a minimum parasite load (+) of 1-4 eggs / field and finally 2.6% with a severe parasite (++++) of> 10 eggs / field. of the parasitic genera found in the tests carried out, we can determine that Toxocara canis, Ancylostomas caninum, Giardia spp. and Eimeria spp. They are gastrointestinal parasites with a zoonotic nature that can be transmitted by several contagion routes and were found in Casipamba, Guaranda and Vinchoa.